1997
DOI: 10.1007/bf01387855
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of plantar defects

Abstract: Abstract. Plantar defects are a challenge for the plastic surgeon; from 1984-1995 59 operations were performed in 57 patients. The radial forearm flap and the latissimus dorsi (LD) flaps were mainly used depending on the amount of tissue loss. Local flaps such as dorsalis pedis and instep flaps were used for smaller defects. The radial forearm flap is ideal in terms of thickness and stability for the sole but limited in its size. The LD flap is a safe procedure especially for severe injuries and osteitis, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Similar to the case of cetineites [1][2][3][4]10] and K-SBC-1, [5] the {Sb 18 O 27 } tubes are presumably stabilized by the strong SbÀO bonds, whereas the overall structure is held together by ionic forces between the negatively charged {SbTe 3 } 3À pyramids and Te 2 2À dumbbells in the tubular interstices, and the rubidium counter cations lined on the inside of the {Sb 18 O 27 } tubes.…”
Section: Angewandte Chemiementioning
confidence: 86%
See 2 more Smart Citations
“…Similar to the case of cetineites [1][2][3][4]10] and K-SBC-1, [5] the {Sb 18 O 27 } tubes are presumably stabilized by the strong SbÀO bonds, whereas the overall structure is held together by ionic forces between the negatively charged {SbTe 3 } 3À pyramids and Te 2 2À dumbbells in the tubular interstices, and the rubidium counter cations lined on the inside of the {Sb 18 O 27 } tubes.…”
Section: Angewandte Chemiementioning
confidence: 86%
“…[1] A variety of additional synthetic cetineite-type phases also reveal optical band gaps in the visible range and electrical semiconductivities. [2] Experimental results [1,3] and theoretical computations [3] have demonstrated that the optical band gaps of the members of the cetineite family with the general formula A 6 [Sb 12 O 18 ][SbX 3 ] 2 (A = K or Na, X = S or Se) vary with the composition of the crystal and tend to decrease with increasing atomic number of both the alkali metal and the chalcogen. It was suggested that these properties may be attributed to an overlap of the sp, d xz , and d yz orbitals of the Sb atoms of chemically different subunits (namely the {Sb 12 O 18 } tubular unit and the {SbS 3 } 3À or {SbSe 3 } 3À pyramids) in an alternating sequence along the crystallographic c axis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Optimal plantar reconstruction provides durable coverage with a favourable aesthetic, while enabling sufficient protective sensation to prevent pressure sores. 9 In the setting of significant tissue loss, especially of the heel, robust coverage is often achieved with skin-grafted muscle flaps, such as serratus, latissimus, and rectus femoris flaps. 10,11 Coverage with microvascular free tissue transfer has the advantage of providing abundant, healthy soft tissue in various thicknesses, depending on the size and location of the defect.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Optimal plantar reconstruction provides durable coverage with a favorable aesthetic and protective sensation to prevent pressure sores. 2 Coverage of lower extremity defects is often achieved with skin-grafted muscle or fasciocutaneous flaps. 1 Free flaps can be innervated to provide sensory feedback, though they have not been shown to be superior in durability and gait.…”
mentioning
confidence: 99%